Health Education Counseling on Lifestyle In Patients With Diabetes Mellitus - Simarmata, Pratiwi Christa; Telova, Yurizki (JURNAL PENGMAS KESTRA (JPK), 2023)
Diabetes mellitus (DM) is a group of metabolic diseases characterized by increased blood glucose levels as a result of decreased insulin secretion, insulin action or both. This can cause long-term damage such as vascular complications and circulatory disorders. Metabolic disorders are often associated with changes in lifestyle and diet. Diabetes mellitus can arise due to defects in the effect of insulin in tissues, and most of this occurs in patients who are overweight. The shift from a traditional lifestyle to a modern lifestyle will increase the risk of developing diabetes mellitus. Lifestyle in this community service includes diet, smoking habits, consuming alcohol, and physical activity. Lifestyle in patients with diabetes mellitus can help manage and control glucose in the blood. The purpose of this community service is to provide counseling about lifestyle on changes in glucose values ??in the blood of diabetes mellitus patients. This community service uses a method with activities starting from the stage of providing material on the concept of diabetes mellitus, lifestyle, management, checking blood glucose values ??and evaluating the results of implementation in diabetes mellitus patients. It is hoped that the results of this community service activity can become learning material for discussion so that community service participants understand better and are able to independently control the value of glucose levels in the blood through lifestyle changes in diabetes mellitus patients.